2015
DOI: 10.1177/147470491501300212
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Cues are More Compelling than Facial Cues in Determining Adults' Reactions towards Young Children

Abstract: Previous research has demonstrated the significant influence that both children's facial features (Lorenz, 1943) and children's cognitive expressions (Bjorklund, Hernández Blasi, and Periss, 2010) have on adults' perception of young children. However, until now, these two types of cues have been studied independently. The present study contrasted these two types of cues simultaneously in a group of college students. To this purpose, we designed five experimental conditions (Consistent, Inconsistent, Mature-Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…In our previous studies (Bjorklund et al, 2010;Hern andez Blasi et al, 2015;Periss et al, 2012), we found that the effect of children's supernatural and natural thinking on adults differed in terms of adults' expressions of positive and negative affect, intelligence assessment, and helplessness feelings towards young children, possibly provoking distinctive caregiving attitudes. To assess such effects, we presented adult participants with pairs of short vignettes, one depicting immature thinking attributed to a young child and a second depicting mature thinking attributed to another child.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…In our previous studies (Bjorklund et al, 2010;Hern andez Blasi et al, 2015;Periss et al, 2012), we found that the effect of children's supernatural and natural thinking on adults differed in terms of adults' expressions of positive and negative affect, intelligence assessment, and helplessness feelings towards young children, possibly provoking distinctive caregiving attitudes. To assess such effects, we presented adult participants with pairs of short vignettes, one depicting immature thinking attributed to a young child and a second depicting mature thinking attributed to another child.…”
mentioning
confidence: 78%
“…The sample consisted of 137 adults (109 female; M age = 21.7 years, SD = 4 years) attending a public urban university in eastern Spain, 36 of whom were part of the Hern andez Blasi et al (2015) sample. Main characteristics of the two subgroups that constituted the sample for this study were basically the same in terms of age and sex distribution, and socioeconomic status (mainly middle class, typical of most college students in Spain).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations